Lower extremity joint angles estimation during gait using ultrasonic sensor network - Sharavana Thevan Pothiya Pillay (2018)
Current methods for gait analysis measurement and monitoring includes camera-based motion analysis system, liquid metal sensors etc. which is highly complex and expensive. Joint flexion and extension angles contributes in monitoring rehabilitation progress and identifying abnormal gait. This paper proposes a low cost, wearable wireless ultrasonic network-based measurement system using readily available components. It is portable, easy to use and unlike the current available system it does not involve complex calibration methods. The system comprises of two ultrasonic transmitter which is a mobile node attached to the subject (hip and ankle joints) and eight receivers, whose locations are known. The proposed ultrasonic measurement system performance was validated against a camera-based motion analysis system to provide a high ranging accuracy, in distance between the transmitters. Using laws of cosine, the joint angles are determined by the acquired distance dataset. The results achieved a root mean square error of 4.02 degrees. By demonstrating the accuracy of the system, it can be the start to further develop other composite system to evaluate and monitor joints. The system will not only be convenient to setup but also be useful in various applications of rehabilitation or sports.